Assessment of biomolecular expression and possible physiological changes during different types of slaughtering - Zaman, Rahela; Rahman, Mohammad Tariqur; Syed Osman Idid, Syed Zahir Idid; Mohd. Salleh, Hamzah (2010)
Traditional practices of slaughtering of chicken or other domestic animals involves knife. However, depending on the ease of handling and religious guidelines, technical differences in the slaughtering procedures exist. Such as if jugular vein will be cut or not. Besides, immediately after slaughtering, the animals are either released (R+) or held tightly (R-) that allows or restricts the movement of the slaughtered animals respectively. To identify possible physiological and biomolecular changes during slaughtering, chicken were slaughtered using a sharp knife. Neck of the chicken were either severed (S+) or not (S-) during slaughtering and bodied were either released immediately after slaughtering (R+) or held tightly allowing restricted movement till the animals were dead (R-). Muscles and liver from slaughtered animals were analyzed to identify possible physiological and biomolecular changes during slaughtering which varies in the mentioned parameters. The expression of acetylcholinesterase (AChE) mRNA, AChe activity, and the content of Zn and Fe were analyzed. Notably acetylcholine (Ach) is a major neurotransmiter (NT) in neuromuscular junction (NMJ) of vertebrate, release of which is related to muscle movement and blood removal; but due to its very short lifespan, it is actually measured indirectly by measuring the enzyme AChe. AChe mRNA expression was analyzed using Reverse Transcription Polymerase Chain Reaction (RT-PCR) and the enzyme activity of AChe was measured spectrophotometrically. The expression of AChe mRNA found to be low in chickens that were slaughtered without severing neck and released immediately after slaughtering, compared to those which were slaughtered by severing the neck and/or held tightly after slaughtering. However, AChe activity was found similar in all samples. As we measured using Atomic Absorption Spectrophotometry (AAS), content of Zn and Fe in muscle and liver in different samples were also found similar range.